Expanding Contraceptive Access for Women With Substance Use Disorders: Partnerships Between Public Health Departments and County Jails. Issue 3 (May 2019) - McNeely, Clea A.; Hutson, Sadie; Sturdivant, Tara L.; Jabson, Jennifer M.; Isabell, Brittany S.
Abstract : Context: Law enforcement has been the primary strategy for addressing the opioid epidemic. As a result, the incarceration rate for women in county jails has increased more than 800% since 1980, and most women inmates struggle with substance use disorders. There is a large unmet need for contraception among women in county jails. Program: The East Region of the Tennessee Department of Health partnered with county correctional facilities to provide comprehensive family planning education and voluntary long-acting reversible contraception (LARC) to women in 15 jails. Implementation: Incarcerated women were invited to attend a comprehensive family planning education session conducted in the jail by health department nurses. The sessions included information on neonatal abstinence syndrome. The nurses explained that the women could receive intrauterine devices, implants, and injectable progesterone while incarcerated and come to the health department for all contraceptive methods upon release. Between January 2014 and June 2017, nurses conducted 182 education sessions, and 794 women received a LARC. Method placement occurred in the jails or at the local health department. No adverse effects were known to have occurred. Evaluation: We collected pilot data to explore the accuracy and the comprehensiveness of the family planning education session and whether the incarcerated women experienced the program as voluntary. All 18 women inmates interviewed reported experiencing the program as voluntary. Using published and administrative data, we roughly estimated that the program prevented between 270 and 460 unintended pregnancies and between 40 and 52 cases of neonatal abstinence syndrome in the first year after the women received a method. This represents a cost savings to Medicaid of $1.4 million. Discussion: The partnership demonstrated the feasibility of providing voluntary comprehensive family planning education and access to highly effective contraception for women inmates who, as a group, face a host of political, socioeconomic, and personal barriers to reproductive health care.